Analysis Of Symbols In The Old Man and The Sea a Novel by Ernest Hemingway - I Gusti Ngurah Octova S (Jurnal Ilmiah Mandala Education (JIME), 2019)
This study aims to analyze important symbols contained in the novel "The Old Man and the Sea", where the symbols often appear but meaning, purpose of the story, and rationale of the author are neglected by the readers. These symbols are representations or interpretations of an idea, personality, object, or abstraction. Data obtained through internet, library research, and the results of related studies from experts. The method used in this study is descriptive objective approach; this approach only focuses on the intrinsic elements of literary work by analyzing and explaining them in detail